KEDUDUKAN SITA PIDANA TERHADAP SITA UMUM KEPAILITAN - Josua Fernando; Susanti Adi Nugroho (Fakultas Hukum Universitas Tarumanagara, 2018)
AbstractThe Court Ruling claim that a debt discharge a bankruptcy inflict a debtor will loose his right to dominate the wealth which include the bankruptcy property. The whole riches of a debt who’s discharge bankruptcy, automatically will be placed to the general confiscation. The general confiscation of the debt property has intend to protect the interest of the creditor of all the deeds of the debt which can disserve the property of a bankruptcy and stop the execution of the debt property with all the creditors to get the debt repayment. The general confiscation itself is a form of confiscation which known in civil law regime especially bankruptcy in legal perspective as a private law. Confiscation in a criminal case aim to prove criminal act. Article 38 of a Criminal Code Procedure regulate that the investigator can undertake the property of confiscation that placed in the general confiscation. However, Article 46 of a Bankruptcy and Suspension Of Obligation For payment Of Debt regulate that all confiscation become vanished when the property has confiscated in the general confiscation. When this two confiscation situated in the property, The confiscation in criminal case will precede the general confiscation. That matter is because of the confiscation in a criminal case is part of public law that aimed to protect our public interest.